Die subtiele aanleg en moontlikhede van die nominale styl: "n Studie in Nuwe-Testamentiese Grieks - Boshoff, P. B. (Hervormde teologiese studies, 1988)
The subtle nature and possibilities of the nominal style: A study New Testament Greek Nominalization as a figure of speech in the New Testament Greek, or any other literature has not yet come to its full value. Nominatization occurs when events in the deep structure are presented in the aurface structuring in nominal form. The nominal form is chosen for the sake of certain fed. The method used to determine the specific contribution of the nominal form is to compare the nominal form with its verbal variant. Five functions of style have been determined for the nominal form: Acceptance ation, Spatialization, Degrading, Manifestation of courtesy and Profiling.